KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DAN KONDISI PSIKOLOGIS SISWA SMP NEGERI 14 PEKANBARU - Sri Rizkillah Nedi; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Violence against children always increases every year. Actions of violence received by children are usually done by the people closest like parents, siblings one blood relation, even people who work at home. However, some parents still consider that such acts of violence as a form of discipline for children. In fact, even the smallest form of violence given to children can have a major impact on the development of children especially for the psychological child. This study aims to determine: 1) the form of violence received by students 2) the psychological condition of students victims of domestic violence. The method used is descriptive quantitative. The population in this study are students of class VIII as much as 235 and sample of 13 students, by using sampling technique that is purposive sampling with medium victim category. Data collection using questionnaire and using likert scale. The results showed: 1) the form of violence that most students accepted is psychic violence that is disepelekan in the form compared with others 2) psychological conditions when viewed based on emotional conditions and the concept itself is in the category of bad and not good. It can be concluded that there is a significant influence between the violence and the psychological condition of victims of violence itself. It is expected that parents and the school to see the development of psychological students especially so as to develop well.Keywords: Violence, Household, Psychological